Association of breakfast styles such as Japanese, Western, and cereals with sleeping habits, eating habits, and lifestyle in preschool and elementary school children - Kuwahara, Mai; Tahara, Yu; Nitta, Lyie; Furutani, Akiko; Mochida, Seiko; Makino, Naomichi; Nozawa, Yuki; Shibata, Shigenobu (Frontiers in Nutrition, 2023)
People have been eating simpler and uncooked breakfasts in recent years as they sleep less. It has already been shown that the individual preference for the daily sleep-wake phase (chronotype) is associated with eating habits and that Japanese-breakfast (JB) eaters are associated with their healthy eating habits. As these studies were analyzed with adult participants, we decided to study these topics in children. Preschoolers and elementary school children (N = 6104, 49.87% boys, 50.13% girls, mean age 5.50 ± 0.02 years, mean BMI 15.39 ± 0.03 kg/m2) have participated in this cross-sectional online survey to answer lifestyle including eating and sleep habits through their mother’s answer. We asked usual breakfast habits by selection from JB, Western-breakfast (WB), cereal-breakfast (CB), or skipping. Results showed that children who consume JB had good sleep habits, including earlier waking and sleeping times both in week and weekend. JB eaten children also consumed variety of protein sources (fish, soy, egg) more frequently. JB eaten children with a morning type showed better sleep and eating habits rather than WB eaten children with evening type pattern. The present results suggest that JB eating habits may be related with good eating and sleep lifestyle even in preschoolers and elementary school children.